Pretheranostic agents with extraordinaryNIRF/photoacoustic imaging performanceand photothermal oncotherapy efficacy - Liu Shi; Zhenzhou Chen; Jiaxin Ou; En Liang; Zhipeng Chen; Qiuyue Fu; Lan Huang; Kui Cheng (Acta Pharmaceutica Sinica B, 2024)
Cervical cancer, the most common gynecological malignancy, significantly and adversely affects women's physical health and well-being. Traditional surgical interventions and chemotherapy, while potentially effective, often entail serious side effects that have led to an urgent need for novel therapeutic methods. Photothermal therapy (PTT) has emerged as a promising approach due to its ability to minimize damage to healthy tissue. Connecting a biothiol detection group to PTT-sensitive molecules can improve tumor targeting and further minimize potential side effects. In this study, we developed a near-infrared fluorescence (NIRF)/photoacoustic (PA) dual-mode probe, S-NBD, which demonstrated robust PTT performance. This innovative probe is capable of activating NIRF/PA signals to enable the detection of biothiols with high emission wavelength (838 nm) and large Stokes shift (178 nm), allowing for in vivo monitoring of cancer cells. Additionally, the probe achieved an outstanding photothermal conversion efficiency of 67.1%. The application of laser irradiation (660 nm, 1.0 W/cm2, 5 min) was able to achieve complete tumor ablation without recurrence. In summary, this seminal study presents a pioneering NIRF/PA dual-mode dicyanoisophorone-based probe for biothiol imaging, incorporating features from PTT for the first time. This pioneering approach achieves the dual objectives of improving tumor diagnosis and treatment.